ChemInform Abstract: From Order to Disorder and Back Again: In situ Hydrothermal Redox Reactions of Uranium Phosphites and Phosphates. Issue 15 (25th March 2013) - Villa, Eric M.; Marr, Connor J.; Diwu, Juan; Alekseev, Evgeny V.; Depmeier, Wulf; Albrecht‐Schmitt, Thomas E.
Abstract Compounds (III)—(VII) are characterized by single crystal XRD, SEM, and UV/VIS/NIR spectroscopy.